A Conceptual Framework of Brand Image, Brand Awareness, Brand Experience, Brand Trust to Purchase Behavior on E-Commerce in Batam - Cindy Ng; Suyono Saputro (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
In this study, by building a conceptual framework of the factors that influence purchase behavior, business actors will be able to evaluate their services to e-commerce customers in Batam. In this conceptual paper, we have summarized the current literature on the existing influence concepts and approaches enabling us to identify a conceptual framework covering all factors that influence customer response, namely brand image, brand awareness, brand experience and brand trust that is felt and by because it will facilitate e-commerce companies to improve their quality in serving consumers in Batam